Gone missing - Castillo, Linda (New York : Minotaur Books, 2012)
Investigating the disappearance of an Amish teenager, chief of police Kate Burkholder and state agent John Tomasetti stumble on a dead body at the same time another girl goes missing, and later discover sinister links to numerous cold cases
Keywords: Burkholder, Kate (Fictitious character) -- Fiction; Women police chiefs -- Ohio -- Fiction; Missing persons -- Investigation -- Fiction; Amish Country (Ohio) -- Fiction